2018
DOI: 10.5194/acp-2017-1024
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can explicit convection improve modelled dust in summertime West Africa?

Abstract: Abstract. Global and regional models have large systematic errors in their modelled dust fields over West Africa. It is well established that cold pool outflows from moist convection (haboobs) can raise over 50 % of the dust over the Sahara and Sahel in summer, but parameterised moist convection tends to give a very poor representation of this in models. Here, we test the hypothesis that an explicit representation of convection improves haboob winds and so may reduce errors in modelled dust fields. The results… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Missing out cold pool outflows can also lead to substantial biases in diurnal cycle of dust (example Kocha et al., 2013) and moisture fluxes over large regions (Garcia‐Carreras et al., 2013). However, it has also been shown that in spite of carrying out simulations at convection permitting scale, surface soil and seasonally changing vegetation characteristics can play a limiting role in properly representing dust aerosol optical depth (Roberts et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Missing out cold pool outflows can also lead to substantial biases in diurnal cycle of dust (example Kocha et al., 2013) and moisture fluxes over large regions (Garcia‐Carreras et al., 2013). However, it has also been shown that in spite of carrying out simulations at convection permitting scale, surface soil and seasonally changing vegetation characteristics can play a limiting role in properly representing dust aerosol optical depth (Roberts et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Next we compare the DEI diurnal differences with a proxy for dust emission, the Dust Uplift Potential (DUP) derived from surface wind observations during at most 5 months (May to September) of the year 2011 (see Roberts et al, 2018, for details) at three Automatic Weather Station (AWS) sites from the Fennec field campaign (Hobby et al, 2013), namely, F‐101 (at the BBM supersite), F‐134, and F‐138, shown in Figure 4 (labels). At sites F‐134 and F‐138, morning DUP exceeds nighttime DUP indicative of the dominant LLJ mechanism, and confirmed by DEI: at both sites the climatological morning/nighttime DEI ratio is of ~2.7.…”
Section: Resultsmentioning
confidence: 99%
“…The IASI observation times, with local equatorial crossing times in the morning at 0930 hr LT and nighttime at 2130 hr LT, match relatively well the times of occurrence of the two dominant dust uplift mechanisms, at least over the Sahara desert: (1) the breakdown of the nocturnal low‐level jet (NLLJ), which drives dust emissions peaking in the midmorning when the LLJ momentum is mixed to the surface after sunrise (Allen et al, 2013; Allen & Washington, 2014; Blackadar, 1957; Heinold et al, 2013; Holton, 1967; Knippertz et al, 2007; Marsham et al, 2011; Marsham, Dixon, et al, 2013; Parker et al, 2005; Schepanski et al, 2009; Todd et al, 2008, 2013; Washington & Todd, 2005; Washington et al, 2006, 2009); (2) density currents, or cold pools, occurring when downdraughts in moist convective systems spread out at the surface whose strong winds generate dust fronts (haboobs) (Allen et al, 2013; Allen & Washington, 2014; Flamant et al, 2007; Knippertz & Todd, 2010, 2012; Marsham et al, 2008; Roberts & Knippertz, 2012; Williams et al, 2009). Cold pools tend to occur preferentially in the afternoon hours but may also occur during a large diurnal window (Allen & Washington, 2014; Emmel et al, 2010; Flamant et al, 2009; Heinold et al, 2013; Knippertz et al, 2007; Knippertz & Todd, 2012; Liu et al, 2018; Marsham et al, 2011; Marsham, Dixon, et al, 2013; Pantillon et al, 2016; Roberts et al, 2018; Schepanski et al, 2009; Vizy & Cook, 2018). Dust emissions over the Sahara have been the subject of many studies over the last years and are now relatively well known: see Knippertz and Todd (2012) for a comprehensive review.…”
Section: Introductionmentioning
confidence: 99%
“…They are also mostly unrepresented in coarse resolution global model simulations used for the Coupled Model Intercomparison Project (CMIP) which rely upon convective parameterization (Marsham et al, 2011;Knippertz & Todd, 2012; A. J. Roberts et al, 2018), although some attempts have been made to parameterize the role of convective downdrafts (Lunt & Valdes, 2002;Cakmur et al, 2004). Similarly, the resolution of all available reanalysis products, including ERA5 at around 30 km grid spacing (Hersbach & Dee, 2016), is too coarse for inclusion of CPOs.…”
Section: Accepted Articlementioning
confidence: 99%
“…Hence, although they are hypothesized to be the dominant dust emission process in the world's largest source region, representation of this process is not surprisingly missing or poor in operational forecasting analyses (Pope et al., 2016; Redl et al., 2016; Sodemann et al., 2015; Trzeciak et al., 2017). They are also mostly unrepresented in coarse resolution global model simulations used for the Coupled Model Intercomparison Project (CMIP) which rely upon convective parameterization (Roberts et al., 2018; Knippertz & Todd, 2012; Marsham et al., 2011), although some attempts have been made to parameterize the role of convective downdrafts (Cakmur et al., 2004; Lunt & Valdes, 2002). Similarly, the resolution of all available reanalysis products, including ERA5 at around 30 km grid spacing (Hersbach & Dee, 2016), is too coarse for inclusion of CPOs.…”
Section: Introductionmentioning
confidence: 99%